Penerapan Model Pembelajaran Word Square dalam Meningkatkan Aktivitas dan Hasil Belajar IPS pada Siswa Kelas V SDN 1 Beringin Raya Tahun pelajaran 2022/2023 - Putri, Aisyah Saindra; Hidayat, Nurdin; Siska, Yulia (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The problems in this study are 1) student learning outcomes are still low, 2) some students are classified as passive in learning 3) when learning students are easily distracted by surrounding conditions and 4) the use of learning models has not varied. One way that can be done to overcome these problems is to apply the word square learning model. The purpose of this study is to increase social studies learning activities and outcomes using the word square learning model in grade 5 students at SDN 1 Beringin Raya Kemiling for the 2022/2023 academic year. The method in this study uses Classroom Action Research (CAR). The subjects in this study were 30 class 5A students at SDN 1 Beringin Raya Kemiling. Data collection techniques in this study were in the form of observation sheets, learning achievement tests, and documentation. The indicator of learning outcomes in this study is to achieve a percentage of 80% of the total number of students who score above the KKM. The research results obtained were (1) student activity in cycle I using the word square learning model obtained a percentage of 64.29% and increased in cycle II to 88.10% and (2) social studies learning outcomes after implementing word square learning every the cycle has increased, where in the pre-cycle the mastery of 50% was obtained, then it increased in cycle I to obtain a percentage of 70% and increased again in cycle II to obtain a percentage of 90%. Based on the results of this study, it can be concluded that by applying the word square learning model it can increase the activity and learning outcomes of Social Sciences students in grade 5 SDN 1 Beringin Raya Kemiling in the 2022/2023 academic year.